RANCANG BANGUN ALAT PEMUTUS ALIRAN LISTRIK RUMAH SAAT TERJADI KEBOCORAN GAS LPG BERBASIS MIKROKONTROLER ARDUINO UNO - Suryadi, Suryadi; Zulkarnaen, Zulkarnaen (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
Design and build a home electrical circuit breaker when LPG gas leaks based on the Arduino Uno microcontroller. In the process of installing LPG gas cylinders that are not right, tools that are not in accordance with Indonesian National Standards and many more. This can cause gas leaks that can trigger explosions, fires and even fatalities. This not only creates benefits and conveniences, especially for housewives, but also the negative impacts caused by using LPG gas cylinders if you are not careful. For that we need an LPG gas leak detector based on the Arduino Uno microcontroller to provide information through warnings or alarms. This study aims to help human life or activities, especially for daily activities in the house such as in regulating environmental security, warning systems and so on. The research methods used are observation methods and literature studies. While the type of research used is experimental research. Based on the test results, it can be concluded that the design of this tool can run on its own because it uses an Arduino microcontroller that has been connected to a sensor to detect LPG gas leaks. Using the MQ6 sensor and performing automatic control of the power cut using a relay and turning on a warning or alarm using a buzzer. . The goal is to prevent fires by cutting off electricity in a house. Knowing the work of the MQ6 sensor, Knowing the work of the relay against power cuts. Knowing how the Arduino Uno microcontroller works.